2018
DOI: 10.21909/sp.2018.03.762
|View full text |Cite
|
Sign up to set email alerts
|

These Problems Sound Familiar to Me: Previous Exposure, Cognitive Reflection Test, and the Moderating Role of Analytic Thinking

Abstract: One of the current topics in research on the Cognitive Reflection Test (CRT) is its growing familiarity among the general public. Surprisingly, Bialek and Pennycook (2017) showed that previous exposure does not diminish the CRT's predictive power in Heuristics and Biases (H&B) tasks, but proposed that the relationship is moderated by analytic thinking, a conjecture tested in the present study. Participants (N = 365) filled in the CRT, Need for Cognition (NFC) scale, and a battery of H&B problems. While the CRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Self-reported prior exposure substantially increases performance in the test (e.g., Bialek & Pennycook, 2017;Haigh, 2016;Stieger & Reips, 2016). However, recent studies suggested that self-reported prior exposure does not diminish the predictive validity of the test (Bialek & Pennycook, 2017;Šrol, 2018b), and nor does actual (not self-reported) prior exposure increase performance on it (Meyer, Zhou, & Frederick, 2018). Despite the reassuring findings on prior exposure, the effect of knowledge of the items on the predictive validity remains unclear.…”
Section: Measuring Cognitive Reflection Without Maths: Development and Validation Of The Crt-vmentioning
confidence: 99%
“…Self-reported prior exposure substantially increases performance in the test (e.g., Bialek & Pennycook, 2017;Haigh, 2016;Stieger & Reips, 2016). However, recent studies suggested that self-reported prior exposure does not diminish the predictive validity of the test (Bialek & Pennycook, 2017;Šrol, 2018b), and nor does actual (not self-reported) prior exposure increase performance on it (Meyer, Zhou, & Frederick, 2018). Despite the reassuring findings on prior exposure, the effect of knowledge of the items on the predictive validity remains unclear.…”
Section: Measuring Cognitive Reflection Without Maths: Development and Validation Of The Crt-vmentioning
confidence: 99%
“…The numeracy scale (NS) contained 2 items from the modified cognitive reflection test (Dudeková & Kostovičová, 2015;Frederick, 2005), where the structure of original items was kept but the content was modified to avoid a common problem with participants recognizing the test items from popular sources (even though it was shown that previous exposure does not significantly affect the results, see Bialek & Pennycook, 2018;Šrol, 2018). One problem with Bayesian reasoning was taken from Zhu and Gigerenzer (2006).…”
Section: Validity Measuresmentioning
confidence: 99%
“…need for cognition, npr. Bialek i Pennycook, 2018;Frederick, 2005;Haran i sur., 2013;Šrol, 2018b;Thomson i Oppenheimer, 2016;Toplak i sur., 2014a), kao i sa sklonošću razmatranja budućih posljedica (engl. consideration of future consequences, npr.…”
Section: Kognitivna Refleksivnost I Razmišljanje Aktivno Otvorenim Umomunclassified